Safety, tolerability, pharmacokinetics, and pharmacodynamics of GLPG1690, a novel autotaxin inhibitor, to treat idiopathic pulmonary fibrosis (FLORA): a phase 2a randomised placebo-controlled trial. Issue 8 (August 2018) - Maher, Toby M; van der Aar, Ellen M; Van de Steen, Olivier; Allamassey, Lisa; Desrivot, Julie; Dupont, Sonia; Fagard, Liesbeth; Ford, Paul; Fieuw, Ann; Wuyts, Wim
Summary: Background: Idiopathic pulmonary fibrosis (IPF) causes irreversible loss of lung function. People with IPF have increased concentrations of autotaxin in lung tissue and lysophosphatidic acid (LPA) in bronchoalveolar lavage fluid and exhaled condensate. GLPG1690 (Galapagos, Mechelen, Belgium) is a novel, potent, selective autotaxin inhibitor with good oral exposure. We explored the effects of GLPG1690 in patients with IPF. Methods: This was a randomised, double-blind, placebo-controlled phase 2a study done in 17 centres in Italy, Ukraine and the UK. Eligible patients were aged 40 years or older, non-smokers, not taking pirfenidone or nintedanib, and had a centrally confirmed diagnosis of IPF. We used a computer-generated randomisation schedule to assign patients 1:3 to receive placebo or 600 mg oral GLPG1690 once daily for 12 weeks. The primary outcomes were safety (adverse events), tolerability, pharmacokinetics, and pharmacodynamics. Spirometry was assessed as a secondary outcome. This trial is registered withClinicalTrials.gov, numberNCT02738801 . Findings: Between March 24, 2016, and May 2, 2017, 72 patients were screened., of whom 49 were ineligible and 23 were enrolled in eight centres (six in Ukraine and two in the UK). Six patients were assigned to receive placebo and 17 to receive GLPG1690. 20 patients completed the study after one in each group discontinued because of adverse events and one in the GLPG1690 group withdrew consent. Four (67%) patients in the placebo group and 11 (65%) in the GLPG1690 group had treatment-emergent adverse events, most of which were mild to moderate. The most frequent events in the GLPG1690 group were infections and infestations (ten events) and respiratory, thoracic, and mediastinal disorders (eight events) with no apparent differences from the placebo group. Two (12%) patients in the GLPG1690 group had events that were judged to be related to treatment. Serious adverse events were seen in two patients in the placebo group (one had a urinary tract infection, acute kidney injury, and lower respiratory tract infection and the other had atrioventricular block, second degree) and one in the GLPG1690 group (cholangiocarcinoma that resulted in discontinuation of treatment). No patients died. The pharmacokinetic and pharmacodynamic profiles of GLPG1690 were similar to those previously shown in healthy controls. LPA C18:2 concentrations in plasma were consistently decreased. Mean change from baseline in forced vital capacity at week 12 was 25 mL (95% CI −75 to 124) for GLPG1690 and −70 mL (−208 to 68 mL) for placebo. Interpretation: Our findings support further development of GLPG1690 as a novel treatment for IPF. Funding: Galapagos.